Система упражнений по развитию крымскотатарской диалогической речи учащихся пятых классов - Яяева, Н.М. (Культура народов Причерноморья, 2013)
В статье поднимаются вопросы разработки системы упражнений в процессе
преподавания крымскотатарского языка в школе. Рассматриваются требования которым должны
отвечать упражнения, а также закрепляются навыки приобретенные в ходе выполнения упражнений. У статті піднімаються питання розробки системи вправ в процесі викладання
кримськотатарської мови в школі. Розглядаються вимоги яким повинні відповідати вправи, а також
закріплюються навички придбані в ході виконання вправ. The article deals with the problems of teaching the Crimean Tatar language to the school pupils
through the system of exercises. It shows the requirements that must be met by exercises. The system of exercises
is shown as a multistoried structure, consisting of productive and perceptive subsystems (for teaching speaking)
and subsystem receptive (for teaching speech understanding) exercises.
The work on the development the dialogical speech of fifth form pupils was conducted in three stages. The
typology of exercises was being developed according to the stages. The system of exercises was being designed
to provide the students prepared and unprepared statement in the dialogue form.
The experiment, conducted in school, was based on natural (real) and artificial (case studies), including nontraditional
team work. To facilitate the student’s mental activity the author has offered the illustrative clarity
method.
We have invented a system of exercises for dialogical speech development. They were being tested as
experimental exercises during the Crimean Tatar language lessons in fifth form groups.